2015
DOI: 10.1038/nrurol.2015.4
|View full text |Cite
|
Sign up to set email alerts
|

Neural reconstruction methods of restoring bladder function

Abstract: During the past century, diverse studies have focused on the development of surgical strategies to restore function of a decentralized bladder after spinal cord or spinal root injury via repair of the original roots or by transferring new axonal sources. The techniques included end-to-end sacral root repairs, transfer of roots from other spinal segments to sacral roots, transfer of intercostal nerves to sacral roots, transfer of various somatic nerves to the pelvic or pudendal nerve, direct reinnervation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 74 publications
(171 reference statements)
0
24
0
Order By: Relevance
“…Although nerve rerouting for voluntary voiding is an attractive concept with potential to benefit patients with neurogenic bladder/sphincter dysfunction, there is currently no clinically applicable technique. 7 Our aim was to further evaluate a somatic-to-autonomic nerve transfer technique. It has been hypothesized that a skin-spinal cord-bladder reflex pathway can be created by rerouting a ventral root containing the somatic motor portion of a reflex arc to a ventral root that controls bladder emptying, while keeping the sensory portion of the somatic reflex arc intact (ie, the dorsal root), and that this new pathway may allow bladder emptying in response to somatic sensory stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although nerve rerouting for voluntary voiding is an attractive concept with potential to benefit patients with neurogenic bladder/sphincter dysfunction, there is currently no clinically applicable technique. 7 Our aim was to further evaluate a somatic-to-autonomic nerve transfer technique. It has been hypothesized that a skin-spinal cord-bladder reflex pathway can be created by rerouting a ventral root containing the somatic motor portion of a reflex arc to a ventral root that controls bladder emptying, while keeping the sensory portion of the somatic reflex arc intact (ie, the dorsal root), and that this new pathway may allow bladder emptying in response to somatic sensory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Key priorities for future research endeavors in this field can be found in a recent review article. 7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This experimental design may have contributed to the gradual long-term changes in CMG parameters noted in most animals. Despite these deficiencies, the animal model developed in this study which utilized weekly/biweekly urethral catheterization in place of indwelling catheters to monitor bladder function in conscious animals should be useful for examining the efficacy of long-term drug treatments, neuromodulation (de Groat and Tai, 2015), intraspinal therapies (Lee et al, 2013), or peripheral nerve re-routing (Gomez-Amaya et al, 2015) in reversing bladder dysfunction after SCI in a non-rodent, larger animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Spasticity, for example, results in involuntary muscle contractions that interfere with precise movement and locomotion[1, 2]. In overactive bladder syndrome, excessive activation of the detrusor muscles of the bladder results in unwanted micturition[3, 4].…”
Section: Introductionmentioning
confidence: 99%